Svar på recension av Svenska Akademiens ordbok på nätet - Bäckerud, Erik; Rosqvist, Bodil (LexicoNordica, 2018)
Petzell, Erik M. (2017): Svenska Akademiens ordbok på nätet. I: LexicoNordica 24, 267–276.